Aberrant splicing and altered spatial expression patterns in fruitless mutants of Drosophila melanogaster. - Goodwin, S; Taylor, B; Villella, A; Foss, M; Ryner, L; Baker, B; Hall, J (2000)
The fruitless (fru) gene functions in Drosophila males to establish the potential for male sexual behaviors. fru encodes a complex set of sex-specific and sex-nonspecific mRNAs through the use of multiple promoters and alternative pre-mRNA processing. The male-specific transcripts produced from the distal (P1) fru promoter are believed to be responsible for its role in specifying sexual behavior and are only expressed in a small fraction of central nervous system (CNS) cells. To understand the molecular etiology of fruitless mutant phenotypes, we compared wild-type and mutant transcription patterns. These experiments revealed that the fru(2), fru(3), fru(4), and fru(sat) mutations, which are due to P-element inserts, alter the pattern of sex-specific and sex-nonspecific fru RNAs. These changes arise in part from the P-element insertions containing splice acceptor sites that create alternative processing pathways. In situ hybridization revealed no alterations in the locations of cells expressing the P1-fru-promoter-derived transcripts in fru(2), fru(3), fru(4), and fru(sat) pharate adults. For the fru(1) mutant (which is due to an inversion breakpoint near the P1 promoter), Northern analyses revealed no significant changes in fru transcript patterns. However, in situ hybridization revealed anomalies in the level and distribution of P1-derived transcripts: in fru(1) males, fewer P1-expressing neurons are found in regions of the dorsal lateral protocerebrum and abdominal ganglion compared to wild-type males. In other regions of the CNS, expression of these transcripts appears normal in fru(1) males. The loss of fruitless expression in these regions likely accounts for the striking courtship abnormalities exhibited by fru(1) males. Thus, we suggest that the mutant phenotypes in fru(2), fru(3), fru(4), and fru(sat) animals are due to a failure to appropriately splice P1 transcripts, whereas the mutant phenotype of fru(1) animals is due to the reduction or absence of P1 transcripts within specific regions of the CNS.